Molecular networking and whole-genome analysis aid discovery of an angucycline that inactivates mTORC1/C2 and induces programmed cell death - Dan, Vipin Mohan; Vinodh, J. S.; Sandesh, C. J.; Sanawar, Rahul; Lekshmi, Asha; Kumar, R. Ajay; Kumar, T. R. Santhosh; Marelli, Uday Kiran; Dastager, Syed G.; Pillai, M. Radhakrishna (ACS Chemical Biology, 2020)
Rediscovery of known compounds and time consumed in identification, especially high molecular weight compounds with complex structure, have let down interest in drug discovery. In this study, whole-genome analysis of microbe and Global Natural Products Social (GNPS) molecular networking helped in initial understanding of possible compounds produced by the microbe. Genome data revealed 10 biosythethic gene clusters that encode for secondary metabolites with anticancer potential. NMR analysis of the pure compound revealed the presence of a four-ringed benz[a]anthracene, thus confirming angucycline; molecular networking further confirmed production of this class of compounds. The type II polyketide synthase gene identified in the microbial genome was matched with the urdamycin duster by BLAST analysis. This information led to ease in identification of urdamycin E and a novel natural derivative, urdamycin V, purified from Streptomyces sp. OA293. Urdamycin E (Urd E) induced apoptosis and autophagy in cancer cell lines. Urd E exerted anticancer action through inactivation of the mTOR complex by preventing phosphorylation at Ser 2448 and Ser 2481 of mTORC1 and mTORC2, respectively. Significant reduction in phosphorylation of the major downstream regulators of both mTORC1 (p70s6k and 4e-bp1) and mTORC2 (Akt) were observed, thus further confirming complete inhibition of the mTOR pathway. Urd E presents itself as a novel mTOR inhibitor that employs a novel mechanism in mTOR pathway inhibition.

Untargeted metabolomics reveals alterations in metabolites of lipid metabolism and immune pathways in the serum of rats after long-term oral administration of Amalaki rasayana - Kumar, Vikas; Kumar, A. Aneesh; Joseph, Vinod; Dan, Vipin Mohan; Jaleel, Abdul; Kumar, T. R. Santhosh; Kartha, Chandrasekharan C. (Molecular and Cellular Biochemistry, 2020)
Amalaki rasayana, a traditional preparation, is widely used by Ayurvedic physicians for the treatment of inflammatory conditions, cardiovascular diseases, and cancer. Metabolic alterations induced by Amalaki rasayana intervention are unknown. We investigated the modulations in serum metabolomic profiles in Wistar rats following long-term oral administration of Amalaki rasayana. Global metabolic profiling was performed of the serum of rats administered with either Amalaki rasayana (AR) or ghee + honey (GH) for 18 months and control animals which were left untreated. Amalaki rasayana components were confirmed from AR extract using HR-LCMS analysis. Significant reductions in prostaglandin J2, 11-dehydrothromboxane B2, and higher levels of reduced glutathione and glycitein metabolites were observed in the serum of AR administered rats compared to the control groups. Eleven different metabolites classified as phospholipids, glycerophospholipids, glucoside derivatives, organic acids, and glycosphingolipid were exclusively observed in the AR administered rats. Pathway analysis suggests that altered metabolites in AR administered rats are those associated with different biochemical pathways of arachidonic acid metabolism, fatty acid metabolism, leukotriene metabolism, G-protein mediated events, phospholipid metabolism, and the immune system. Targeted metabolomics confirmed the presence of gallic acid, ellagic acid, and arachidonic acid components in the AR extract. The known activities of these components can be correlated with the altered metabolic profile following long-term AR administration. AR also activates IGF1R-Akt-Foxo3 signaling axis in heart tissues of rats administered with AR. Our study identifies AR components that induce alterations in lipid metabolism and immune pathways in animals which consume AR for an extended period.
Keywords: Amalaki rasayana; Ayurvedic medicines; Leukotriene metabolism; Lipid metabolism; Metabolic profiling